Relationship between brain activity and voiding patterns in healthy preterm neonates. Issue 2 (April 2016) - Zhang, Y.S.; Huang, C.X.; Wen, J.G.; Sheng, G.Y.; Cheng, X.Y.; Zhang, Q.
Summary: Introduction: It remains controversial as to whether the brain affects voiding control in preterm newborns. Constant bladder volume has previously been thought to induce bladder voiding in neonates, with no influence from the brain. Lately, there has been distinct evidence for an existing connection between the central nervous system and bladder voiding in preterm infants, as the voiding reflex arouses neonatal children. Video electroencephalography (EEG) is useful for recording bioelectrical activity of the cerebral cortex and exploring its relationship with voiding patterns in preterm neonates. Objective: The objective was to investigate the relationship between voiding patterns and brain activity in healthy preterm neonates by using video-EEG. Study design: Forty-seven healthy preterm neonates (16 females) with a mean postconceptional age (PCA) of 34.1 ± 1.8 weeks were divided according to PCA into three groups: Group I (31–33 weeks, n = 13); Group II (33–35 weeks, n = 14); and Group III (35–37 weeks, n = 20). Video-EEG data from eight cortical regions were recorded from 08:00–12:00, along with 4-hour free voiding patterns and status at voiding (awake/sleep). Results: In Group I, the voiding frequency (VF) was significantly higher and the voiding volume (VV) was significantly lower than in the other groups. There were no significant differences in bladder capacity (BC), bladder capacity/birth weight (BC/BW), postvoiding residual/bladder capacity (PVR/BC), or urinary flow rate (UFR) among the three groups. The Fp1-T3 and Fp2-T4 lead amplitudes significantly differed in Group I and Group II at 5 s before (pre-5), during, and after voiding (post-5). The Fp2-C4 total and theta band lead amplitudes significantly differed across all urination states among the groups. There were no significant differences in electroencephalography frequency among the groups in any urination state. Discussion: There were no significant differences in BC, BC/BW, PVR/BC, or UFR among the three groups, indicating slow bladder function development in preterm neonates. In this study, the EEG amplitude changed in certain pairs of electrodes. These changes might indicate the degree of bladder sensor maturation along with an increasing PCA. This study further suggests that the brain changes in preterm neonates during quiet sleep voiding prominently occur in the right prefrontal cortex and central region. Conclusions: In preterm neonates, bladder voiding during quiet sleep was accompanied by cortical arousal that might have emanated from a lower center. Table Four-hour voiding observations in the three groups. Group I Group II Group III P BW (kg) 1.41 ± 0.28 1.70 ± 0.36 1.90 ± 0.49* 0.00 VF (times) 4.43 ± 0.98* 3.29 ± 0.49 2.79 ± 1.19 0.01 VF/QS (times) 2.46 ± 1.05 1.64 ± 1.08 1.00 ± 0.92* 0.00 VV (ml) 6.34 ± 4.15* 9.39 ± 5.30 9.18 ± 6.28 0.04 BC (ml) 9.08 ± 4.61 10.58 ± 5.36 11.50 ± 6.15 0.42 BC/BW 7.14 ± 4.35 5.53 ± 2.37 6.59 ± 3.17 0.43 PVR/BC 0.24 ± 0.17 0.19 ± 0.18 0.17 ± 0.15 0.31 UFR (ml/sec) 2.41 ± 1.60 1.65 ± 0.96 1.99 ± 1.26 0.26 Postconceptional ages: Group I, 31–33 weeks; Group II, 33–35 weeks; Group III, 35–37 weeks. BC/BW, bladder capacity/birth weight (BC was defined as the sum of VV and PVR); BW, birth weight; PVR/BC, postvoiding residual volume/bladder capacity; UFR, urinary flow rate; VF, voiding frequency; VF/QS, voiding frequency/quiet sleep; VV, voided volumes. * P < 0.05.